Changes in tuberculosis burden and its associated risk factors in Guizhou Province of China during 2006-2020: an observational study - Yun Wang; Huijuan Chen; Xiaoqi Zeng; Long Liao; Xiaolong Lu; Aihua Zhang (BMC, 2024)
Abstract Background Understanding the trends of tuberculosis (TB) burden and its risk factors at the provincial level in the context of global End TB targets is crucial to identify the progress and challenges in TB control. We aimed to estimate the burden of TB and risk factors for death from 2006 to 2020 for the first time in Guizhou Province, China. Methods Data were collected from the national TB surveillance system. Four indicators of TB burden and their corresponding age-standardized rates (ASRs), including incidence (ASIR), prevalence (ASPR), mortality (ASMR) and disability-adjusted life years (DALYs) (ASDR), were estimated and stratified by year, age, gender and prefecture. Temporal trends of ASRs were presented by locally weighted regression, and the annual percentage change was calculated. The correlation between gross domestic product (GDP) per capita and ASRs was evaluated by Pearson correlation analysis. The associated risk factors for death in PTB patients were determined using logistic regression models. Results A total of 557,476 pulmonary TB (PTB) cases and 11,234 deaths were reported, including 2233 (19.9%) TB specific deaths and 9001 (80.1%) deaths from other causes. The 15-year average incidence, prevalence and mortality rates were 94.6, 102.6 and 2.1 per 100,000 population, respectively. The average DALY rate was 0.60 per 1000 population. The ASIR and ASPR have shown downward trends since 2012, with the largest percentage decrease in 2020 (ASIR: -29.8%; ASPR: -30.5%). The number in TB specific deaths consistently decreased during the study period (P<0.001), while the increase in deaths from other causes drove the overall upward trend in ASMR and ASDR. Four ASRs remained high in males and 5 prefectures. GDP per capita was negatively associated with the ASIR, ASPR and ASDR (P<0.05). Among PTB patients, men, patients with no fixed job, those with a low GDP level, patients with increasing age, those previously treated, those with severe symptoms, those transferred in and those receiving directly observed treatment were more likely to suffer death. Conclusion Guizhou has made progress in reducing PTB cases and TB specific deaths over the last 15 years. Targeted interventions are needed to address these risk factors for death in PTB patients and high-risk areas.